Editorial - Ahmed, Tahera (Bangladesh Journal of Bioethics, 2018)
Announcement for the 20th Asian Bioethics Conference (ABC20) to be held on 22-25 Nov, 2019 at Dhaka, Bangladesh by Prof. Shamima Lasker, Secretary General, Bangladesh Bioethics Society .The conference will be organized by Bangladesh Bioethics Society (BBS) in cooperation with DGHS, Ministry of Health and Family Welfare, People’s Republic of Bangladesh and in conjunction with ABA and Eubios Ethics Institute, Thailand, New Zeeland and Japan. It will provide opportunity for all scholars around the world to present their research work, maximize networking opportunities, and learn about the latest information and methodologies on bioethics. Abstract Submission will be open from 1st March, 2019. Abstract Submission Deadline: August 15, 2019. Please send your abstract to Prof MA Shakoor at: shakoor.abc2019@gmail.com and rafe.dr@gmail.com and cc to splasker04@yahoo.com for your all communication. Come and join us in Dhaka the old Moghul city!